Ideological hybrids: the contrary case of Tory anarchism. Issue 2 (3rd May 2016) - Franks, Benjamin
Abstract: This article provides an account of ideological hybridity. It describes and categorizes four main types of ideological hybrid in order to examine a range of sub-ideologies and cross-breeds but concentrates on identifying and assessing the particular phenomena described as conservative (or 'Tory') anarchisms. The article demonstrates how an ideological hybrid's morphological relationship to its parent ideologies can alter in different geographical or historical contexts. Using this model, it argues that some differences between conservatism and anarchism are overstressed (such as those over the role of the state and individual rights), whilst some important similarities are often overlooked, namely those surrounding their political epistemologies. However, because apparently shared concepts are structured next to radically different core principles (defence/rejection of hierarchies and prioritizing/negation of dominant economic institutions), these shared principles are interpreted in radically different ways. As a result, conservative anarchism is a deeply unstable hybrid rather than an innovative new ideological form. It is one which, in most contexts, stabilizes into a form of conservatism rather than a form of anarchism.